Safety and Effectiveness of Oral Methylprednisolone Therapy in Comparison With Intramuscular Adrenocorticotropic Hormone and Oral Prednisolone in Children With Infantile Spasms - Zhu, Hong-Min; Yuan, Chun-Hui; Luo, Meng-Qing; Deng, Xiao-Long; Huang, Sheng; Wu, Ge-Fei; Hu, Jia-Sheng; Yao, Cong; Liu, Zhi-Sheng (Frontiers in Neurology, 2021)
Background and purpose: To assess the safety and effectiveness of oral methylprednisolone (oMP) in comparison with intramuscular adrenocorticotropic hormone (imACTH) and oral prednisolone (oP) therapies in children with infantile spasms (IS). Methods: In this prospective, open-label, non-blinded, uncontrolled observational study, children (aged 2–24 months) with newly diagnosed IS presenting with hypsarrhythmia or its variants on electroencephalogram (EEG) were included. And was followed by imACTH, oP, or oMP (32–48 mg/day for 2 weeks followed by tapering) treatments. Electroclinical remission/spasm control, relapse, and adverse effects were evaluated in the short-term (days 14 and 42) and intermediary-term (3, 6, and 12 months) intervals. Results: A total of 320 pediatric patients were enrolled: 108, 107, and 105 in the imACTH, oMP, and oP groups, respectively. The proportion of children achieving electroclinical remission on days 14 and 42 was similar among the three groups (day 14: 53.70 vs. 60.75 vs. 51.43%, P = 0.362; day 42: 57.55 vs. 63.46 vs. 55.34%, P = 0.470). The time to response was significantly faster in the oMP group (6.5 [3.00, 10.00] days vs. 8.00 [5.00, 11.00] days for imACTH and 8.00 [5.00, 13.00] days for oP, P = 0.025). Spasm control at 3, 6, and 12 months was also similar in the three groups (P = 0.775, 0.667 and 0.779). The relapse rate in the imACTH group (24.10%) was lower than oMP (30.77%) and oP groups (33.33%), and the time taken for relapse in the imACTH group (79.00 [56.50, 152.00] days) was longer than oMP (62.50 [38.00, 121.75] days) and oP groups (71.50 [40.00, 99.75] days), but the differences were not statistically significant (P = 0.539 and 0.530, respectively). The occurrence of adverse effects was similar among the three groups. Conclusions: The short and intermediary-term efficacy and recurrence rates of oMP are not inferior to those of imACTH and oP for the treatment of IS. Significantly, the time to achieve electroclinical remission with oMP was quicker than that with imACTH and oP. Considering its convenience, affordability, and the absence of irreversible side effects, oMP can serve as a form of ﬁrst-line treatment for newly diagnosed IS.